Analisis Karakteristik Maggot dan Kasgot yang dihasilkan dari Proses Biokonversi Sampah Organik pada Bank Sampah Desa Bengle, Karawang - Sari, Gina Lova; Laksono, Rommy Andhika; Hadining, Aulia Fashanah; Rohmana, Andini Siti; Wicaksono, Bayu Aji (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2022)
Organic waste bioconversion through maggot cultivation is believed to be a solution for managing organic waste based on a circular economy. Maggot cultivation has been widely carried out by Bank Sampah managed by the community in Indonesia, one of which is located in Bengle Village, Karawang District. Bank Sampah (BS) of Bengle Village has been able to reduce organic waste and produce Kasgot, reaching 75.00% and 25.00%, respectively. This study aims to examine nutritional content of maggot and characteristics of kasgot produced by BS of Bengle Village. The results showed that fresh and dried maggot contained quite high fat and protein, of 38.99%; 29.65% and 40.94%; 34.75%, respectively. These values make both maggots feasible as sources of animal fat and protein for poultry. Furthermore, Kasgot contains N-total, P2O5, K2O, Fe, and Pb each of 3.98%; 2.80%; 3.32%; 332.18 ppm; and 0.26 ppm has met the minimum specifications for solid organic fertilizer and compost from organic waste. However, the C/N ratio (6.40) and moisture content (22.77%) did not meet these standards and indicated that Kasgot was not stable as an organic fertilizer. Despite that, the quality of Kasgot can be improved through advanced fermentation processes such as vermicomposting so that it can be used as a substitute for inorganic fertilizers for plant growth and improve soil conditions.